Reducing Unnecessary Brain Computed Tomography Scan in a Tertiary Center - Mohamed Abdoun; Abdelmoneim Mahgoub; J. Motwali (Dr. Sulaiman Al Habib Medical Journal)
Brain Computed Tomography (CT) is routinely requested before Lumbar Puncture (LP) to rule out increased intracranial pressure. However, normal brain radiography does not abate the risk of herniation and unnecessarily delays the course of treatment. Thus, the primary aims of this study were to evaluate the frequency of brain CT scan abnormalities in children with suspected meningitis and to assess under what circumstances such changes are expected, with a secondary aim of reducing unnecessary brain CT scans. A retrospective study was conducted on 86 children with suspected meningitis before LP. Patients who underwent CT scans on suspicion of other neurological disorders were excluded. CT scan in 94.2% (n = 81) cases were reported normal. 40% (n = 2) cases with abnormal CT scan had altered sensorium as compared to 7.4% (n = 6) with normal CT scan (p = 0.01). Furthermore, 46.5% of neuroimaging requests were not indicated. Herniation was not reported in our study. We conclude that indiscriminate brain CT scans have a limited role without clinical indications. In agreement with previous research, we recommend that requests for brain CT prior to LP be made on particular indications, as per clinical guidelines. Future prospective studies and re-auditing of practice continue to expand this body of evidence.